Kebertahanan Pengusaha Coffee Shop pada Masa Pandemi Covid-19 (Studi Kasus Empat Pengusaha Coffee Shop di Kecamatan Denpasar Barat) - Naibaho, Hizkia; Kaler, I Ketut; Suarsana, I Nyoman (Sunari Penjor : Journal of Anthropology, 2024)
This research aims to understand the sustainability of coffee shop entrepreneurs during the Covid-19 pandemic, with a focus on how they adapt to social and economic changes The results of the study show that coffee shop entrepreneurs experience various challenges during the Covid-19 pandemic, such as decreased number of customers and revenue, increased operational costs, and uncertainty about the future. The main findings show that coffee shop entrepreneurs who have survived during the Covid-19 pandemic apply different adaptation strategies, including expanding delivery services, adjusting menus, and strengthening branding through social media. In addition, the entrepreneurs also face challenges in maintaining the health of their employees and customers. This study contributes to an understanding of how coffee shop entrepreneurs can survive in crisis situations and provides advice for creative entrepreneurs in the future.